COMPARISON OF THE ACTIVATION OF GIGANTOCHLOA APUS TO INCREASE THE ADSORPTION ABILITY OF MEDICAL LIQUID WASTE - Setyarini, Putu Hadi; Iksandy, Jemmie; Fachrezi, M. Qashmal; Sonief, Achmad As'ad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Medical facilities are exposed to substantial health and safety hazards as a result of the existence of perilous substances such as germs, viruses, and mold. The integration of drug use courses in medical education is hindered by constraints such as time limitations, a scarcity of well-informed personnel, and insufficient institutional backing. In order to mitigate these dangers, a comprehensive assessment of the risks, effective instruction, and stringent procedures are required. Effective waste management systems and precise detection of influent are crucial. Activated carbon, a highly porous material, is extensively utilized as an adsorbent in several industrial applications. Bamboo charcoal, a desirable lignocellulosic substance, is employed in the manufacturing process of activated carbon. The objective of the study was to generate and examine activated carbons obtained from Gigantochloas Apus (GA) through the utilization of sodium hydroxide (NaOH) and sodium chloride (NaCl) activation methods. The study determined that was the most efficient activating agent for achieving ideal ash content characteristics, resulting in the lowest ash percentage of 6.21%. The acidity of medical liquid waste is increased and its adsorption duration is extended by activating GA with NaCl and NaOH.